INTERACTION OF PESTICIDES WITH MEMBRANE STRUCTURES OF HEPATOCYTES: Ochilov K.R. - Bukhara State Medical Institute named after Abu Ali ibn Sino. Bukhara. Uzbekistan., Ochilov K.R. (Лучшие интеллектуальные исследования, 2024)
Currently, the protection of public health is an urgent problem on a global scale. The predominant part of environmental pollutants are pesticides, without the use of which the promising development of agriculture is impossible. According to the World Health Organization (WHO), from 500 thousand to 2 million people are exposed to pesticide poisoning every year in the world, and 40 thousand cases end in death.